Gebed en Ou-Testamentiese teologie - D. F. O'Kennedy (Acta Theologica)
Prayer should be an intrinsic part of theology because the way in which people understand the nature of God determines the nature and content of their prayers. This article poses the following question: In which way is prayer discussed in Old Testament theologies? This question is discussed by an investigation into ten prominent Old Testament theologies: Eichrodt; Vriezen; Von Rad; Zimmerli; McKenzie; Westermann; Clements; Childs; Preuss; en Brueggemann. It is significant that the systematic discussion of prayer is ignored or neglected in many theologies, especially theologies of English scholars. There are a few deficiencies in theologies discussing prayer, inter alia the negligence of non-Psalmic prayers and intercessory prayers.